Comparison of Patient-Specific Quality Assurance of 6 MV and 10 MV VMAT plan at Isocenter using Improved Gamma Evaluation Algorithm - JITENDRA NIGAM; Piyush Kumar; P SINGH (Iranian Journal of Medical Physics, 2022)
Introduction: To compare Patient-Specific Quality Assurance (PSQA) of 6 MV and 10 MV Volume Modulated Arc Therapy (VMAT) plans performed with Electronic Portal Imaging Device (EPID) kept at Isocenter 100 cm (Source to Imager Distance (SID)) using an Improved Gamma Evaluation algorithm. Material and Methods: Previously treated patients with 6 MV IMRT for Pelvic cancers were planned, on Eclipse TPS, with 6 MV and 10 MV photon beams using VMAT technology. The PSQA was performed using EPID and investigated the effect on Area Gamma, Maximum Gamma & Average Gamma. Results: The mean Area Gamma passing rate (%GP±Standard Deviation(σ)) for 6 MV was 97.06±3.70, 95.42±5.31, 90.93±7.29, 86.55±9.10 and for 10 MV  97.14±6.08, 95.8±8.47, 94.62±9.45, 91.97±13.50 using the criteria 3%/3 mm, 3%/2 mm, 2%/3 mm, 2%/2 mm respectively.  Similarly, for mean Maximum Gamma value for 6 MV was 2.50±0.89, 2.72±0.94, 3.32±1.13, 3.56±1.02 and for 10 MV 2.17±0.62, 2.42±0.72, 2.84±0.90, 3.26±0.94 respectively. For mean average gamma, value for 6 MV was 0.36±0.09, 0.42±0.10, 0.45±0.12, 0.53±0.13 and for 10 MV was 0.27±0.16, 0.32±0.19, 0.34±0.20, 0.41±0.24. Conclusion: There is a marked difference between Area Gamma Passing Rate of 6 MV and 10 MV photon beam. The gamma criteria of 3%/2 mm with a 5% Threshold limit and 95% Area Gamma Passing Rate can be used for PSQA using EPID at Isocenter for 6 MV and 10 MV photon beam. There is no marked significant difference in values of mean Maximum Gamma and mean Average Gamma for 6 MV and 10 MV photon beams PSQA